PEMAKNAAN TONE INDICATORS OLEH KOMUNITAS NEURODIVERGENT : Studi Netnografi Terhadap Komunitas Neurodivergent Di Twitter - Khansa Ayu Fadhila (2021)
Researcher noticed and acknowledged the use of specific textual cues known as "tone indicators" by the neurodivergent community on Twitter. Tone indicators act as paralinguistic cues in text-based communication and help provide context while also clarify the tone in the text messages. This communication phenomenon raises the researcher's curiosity and attempt to understand more about the meaning of tone indicators themselves by the neurodivergent community and study their benefitsin online communication. This research uses netnography method while the datas are collected through observations and in-depth interviews. Netnography was chosen to help review and gain information of a community culture on social media. From this study, researcher found that tone indicators have important meanings as paralinguistic cues that helped giving context in text-based communication. The roles and benefits of these cues are; 1) clarifying meaning in messages, 2) emphasizing emotion and expression of a message, 3) reduce misunderstanding and conflict, and 4) provide a sense of security and comfort while interacting within communities in social media.